The external forces in male world cup alpine skiing - Gilgien, M.; Spörri, J.; Kröll, J.; Crivelli, P.; Cabri, J.; Müller, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The external forces acting on alpine skiers determine their trajectory and, therefore, indirectly their performance. Furthermore, external forces are known to be related to injury risk. Despite decades of biomechanical research, a comprehensive understanding of forces acting in World Cup ski racing is lacking. Hence, the aim of the current study was to assess the external forces acting on male World Cup (WC) alpine skiers in the disciplines giant slalom (GS), super-G (SG) and downhill (DH). Methods: During several WC races (14 GS, 5 SG and 5 DH runs) a forerunner (former WC or current Europa Cup skier) was equipped with a differential global navigation satellite system (dGNSS) tracking the skiers head trajectory at a frequency of 50Hz. The snow surface of the course was captured by static dGNSS and a digital terrain model was reconstructed (Gilgien et al., 2008). The digital terrain model in combination with a pendulum model attached to the helmet trajectory was used to derive ground reaction force (FG), ski - snow friction (FF) and air drag (FD) were derived (Gilgien et al., 2013). In addition, the parameters energy dissipation due to ski - snow friction ED(FF) and energy dissipation due to air drag ED(FD) were calculated. Finally, the differences between discipline medians were tested using an ANOVA, Kruskal - Wallis test (p= 0.01), followed by a Friedman`s test. Results: The forces are given in body weight (BW): FG was largest for GS (1.46±1.04), followed by SG (1.42±0.86) and DH (1.21±0.53). A similar ranking was found for FF (GS: -0.20±0.27; SG: -0.15±0.19; DH: -0.10±0.15). In contrast, the median of FD was largest for DH (0.13±0.12), followed by SG (-0.09±0.06) and GS (-0.07±0.05). The energy dissipation values are given in BW•m: ED(FD) was largest for DH (-0.06±0.07), followed by SG (-0.04±0.03) and GS (-0.02±0.02). No differences were observed for ED(FF) between GS (-0.07±0.09) and SG (-0.07±0.09), while ED(FF) was smaller for DH (-0.05±0.08). Discussion: This study illustrated that the athletes` loading (FG) is largest in GS, followed by SG and DH probably due to a higher turn frequency (Gilgien et al. 2014). The main factor causing energy dissipation in DH was found to be FD, while in GS and SG FF causes the major part of energy dissipation. This might be explained by the fact that in DH speed is higher and courses consist of more straight skiing (Gilgien et al. 2014).